Determination of Ethanol in Vinegar and Beverage by Gas Chromatography: A Validated Method for Halal Verification - Rohyami, Yuli; Wijaya, Aprisilia Risky; Ruwindya, Yorfan (Indonesian Journal of Chemical Analysis (IJCA), 2024)
Validation of the method for determining ethanol in vinegar and beverages has been carried out in the linearity range of 0.05-1% using GC-FID. This research was carried out using an internal standard solution and without an internal standard solution. The research aims to validate the linearity of ethanol determination at low concentration levels. This validation is useful to ensure that the ethanol test method in the sample can be detected at low concentration levels. In the halal authentication process, the maximum limit for ethanol content is 5%. The method validation results confirm that in the concentration range 0.05-1% it has good linearity with a correlation coefficient (R) without the addition of internal standards and with the addition of standard solutions being 0.9972 (R2=0.9943) and 0.9952 (R2=0.9905). The results of the analysis of variance (ANOVA) test with a 95% confidence interval and 9 degrees of freedom F-count (0.0141) < F-critical (0.3146) show that the range 0.05-1% corresponds to the limit of linearity. The results of the ANOVA test with a 95% confidence interval with df=6 show the F-test value (0.0879) < F-critical (0.2334) indicating that the two proposed methods have high precision and no significant differences. Both methods also have high accuracy and no significant differences in accuracy as shown by the results of the ANOVA test with a 95% confidence interval and degrees of freedom = 6 showing the F-test value (1.5204) < F-critical (4.2839). It is recommended that the results of this validation be useful in the halal verification process for vinegar and beverage products.